Nonsense mutation R1162X of the cystic fibrosis transmembrane conductance regulator gene does not reduce messenger RNA expression in nasal epithelial tissue. - Rolfini, R (1993)
Cystic fibrosis (CF) patients bearing the premature translation termination mutation (nonsense mutation) W1282X present severe pulmonary and pancreatic disease, whereas patients carrying other nonsense mutations such as G542X, R553X, S1255X, R1162X, and W1316X show a severe pancreatic but mild pulmonary illness. CF gene expression was found absent in respiratory tissues with mutations R553X and W1316X, which led to the hypothesis that the absence of the gene product in the lung is more favorable than the presence of an altered one. We asked whether or not all the nonsense mutations characterized by mild pulmonary disease phenotypes do present the absence of CF gene expression. We therefore investigated gene expression at the mRNA level in respiratory cells obtained from nasal polyps from a patient homozygous for the R1162X mutation. Gene expression was studied by amplification with polymerase chain reaction of segments of the CF transmembrane conductance regulator cDNA that was obtained by reverse transcription of RNA. Semiquantitative analysis was performed by Northern analysis. By comparing the data obtained from polyps deriving from non-CF subjects and a CF patient homozygous for dF508 mutation, it is shown that no reduction of CF gene expression is evident in R1162X respiratory tissue. We conclude that CF nonsense mutations have heterogeneous mechanisms of gene expression.